1988
DOI: 10.1021/jo00238a011
|View full text |Cite
|
Sign up to set email alerts
|

Tetra-n-butylammonium oxone. Oxidations under anhydrous conditions

Abstract: Tetra-n-butylammonium Oxone, readily prepared as a white solid from commercially available Oxone, performs oxidations in anhydrous methylene chloride. Under these conditions, sulfides are oxidized to sulfones in the presence of amines, ketones, esters, carbamates, olefins, and hydroxyl functionalities. Very acid-labile groups such as dimethyl ketals and THP ethers require buffering with anhydrous sodium carbonate. Reactions may be worked up either by direct chromatography of the reaction mixture or by two-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(58 citation statements)
references
References 1 publication
1
55
0
2
Order By: Relevance
“…These include ammonium peroxymonosulfate, tetra-n-butylammonium peroxymonosulfate (TBA-OX), tetra-n-pentylammonium peroxymonosulfate, and tetra-n-hexylammonium peroxymonosulfate. [27,28] In 1985, Dehmlow et al reported a methodology to prepare TBA-OX and other tetraalkylammonium salts of peroxymonosulfate by cationic exchange from Oxone. [27] However, only in 1988 did Trost and co-workers popularize TBA-OX as an organic soluble form of Oxone that was capable of oxidizing sulfides to sulfones under anhydrous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These include ammonium peroxymonosulfate, tetra-n-butylammonium peroxymonosulfate (TBA-OX), tetra-n-pentylammonium peroxymonosulfate, and tetra-n-hexylammonium peroxymonosulfate. [27,28] In 1985, Dehmlow et al reported a methodology to prepare TBA-OX and other tetraalkylammonium salts of peroxymonosulfate by cationic exchange from Oxone. [27] However, only in 1988 did Trost and co-workers popularize TBA-OX as an organic soluble form of Oxone that was capable of oxidizing sulfides to sulfones under anhydrous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting suspension was filtered through a pad of celite, and the filtrate was concentrated under reduced pressure. The residue was purified by silica gel flash column chromatography (5:1 hexane/EtOAc) to afford 10 (2.70 g, 90%) as a colorless oil: [α] 9, 62.7, 61.3, 61.2, 34.9, 28.3, 26.0, 25.9, 25.8, 18.3, 16.8, − 5.3, − 5.4 ((3-Methylbut-2-en-1-yl)sulfonyl)benzene (12) To a solution of 1-bromo-3-methyl-2-butene (100 μl, 0.859 mmol) in dimethylformamide (8.6 …”
Section: Enzyme Assaysmentioning
confidence: 99%
“…TBA-OX was prepared from commercially available Oxone by a procedure described in the literature [14] . Simply extracting an aqueous solution of oxone and tetra-n-butylammonium bisulfate with dichloromethane, drying, and evaporating gave the product.…”
Section: Experiments Section General Remarksmentioning
confidence: 99%
“…TBA-OX was first used for the oxidation of sulfides and sulfur-containing amino acid derivatives [14] but has never before been used for the oxidation of alcohols.…”
mentioning
confidence: 99%